Antibacterial and antioxidant activities of lanna medicinal plants used in mahoog formula - Sarinya Kadchumsang (2018)
© 2015, International Journal of Pharmacy and Pharmaceutical Science. All rights reserved. Objectives: Antibacterial and antioxidant activities of Lanna medicinal plants used in Mahoog formula were investigated. Methods: Dried powders of twenty five Lanna medicinal plants were extracted with ethanol using soxhlet’s apparatus and with water by decoction method to obtain ethanolic and water extracts, respectively. Each extract was evaluated for antibacterial activity by agar diffusion technique and antioxidant activity by 2,2´-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) free radical scavenging assay, 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay and ferric reducing antioxidant power (FRAP) assay. Results: Most ofLanna medicinal plant extracts were active against gram-positive bacteria. The extract of Caesalpinia sappan (heart wood) showed the highest inhibitory effect on Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa. Interestingly,the extract of Sindora siamensis (stem) exhibited potent activity against S. aureus as same as C. sappan with MIC and MBC values of 0.049 and 0.098 mg/ml, respectively. The antioxidant activities revealed that the extract of C. sappan and S. siamensis possess significant free radical scavenging and reducing power. Conclusion: Most of the medicinal plants consisted in Mahoog formula revealed antioxidant and antibacterial activities. Thedata obtained from the study will be used as a scientific evidence to support the pharmacological properties of medicinal plants used in Mahoog formula.